SLANG WORD IN SONG LYRICS BY “BILLIE EILISH ON WHEN WE ALL FALL ASLEEP, WHERE DO WE GO? ALBUM” - Riris Siahaan; Herman Herman; Christian Neni Purba (Journal of English Language and Education, 2021)
This research is aimed to analyse the slang used in the song lyrics by Billie Eilish in an album. Problems raised in this research are: (1) What kinds of Slang Words used in Billie Eilish on When We All Fall Asleep, Where Do We Go? Album (2) What is the most dominant type of Slang Words in Billie Eilish on When We All Fall Asleep, Where Do We Go? Album. This research used Yule’s theory (2010) about types of Slang Words. The method used in this research is qualitative method. Content analysis was applied in this research. The data were the album entitled When We All Fall Asleep, Where di We Go? After conductiong the data analysis, the researchers found six types of Slang Words in lyrics of Billie Eilish they are: Coinage, Borrowing, Compounding, Blending, Clipping, Derivation. The data were collected by listening to 13 songs by Billie Eilish and reading the lyrics of the songs. There were 159 Slang Words, 21 Slang Coinage, 1 Slang of Borrowing, 1 Slang of Compounding, 102 Slang of Blending, 30 Slang of Clipping, 4 Slang of Derivation. So, Slang Words is something good to learn